Aggregate accounting earnings, special items and growth in gross domestic product: evidence from Australia. (22nd October 2021) - Zhang, Lijuan; Fargher, Neil
Abstract: Macroeconomic analysts have been found to not take full account of aggregate accounting earnings when forecasting future growth in US gross domestic product (GDP). Using Australian data, we confirm this finding and find that the association between aggregate earnings and GDP growth is robust to inclusion of economic factors to capture the importance of the resources sector and the open nature of the Australian economy. We also find that this association is higher in the post‐IFRS period. Finally, we document that both aggregate earnings and negative special items are important for explaining future GDP growth and forecast errors.